Solubility and Dissolution Enhancement of Ebastine by Surface Solid Dispersion Technique - Hussein, Lina S.; Al-Khedairy, Eman B. H. (Iraqi Journal of Pharmaceutical Sciences, 2021)
Ebastine (EBS) is a non-sedating antihistamine with a long duration of action. This drug has predominantly hydrophobic property causing a low solubility and low bioavailability. Surface solid dispersions (SSD) is an effective technique for improving the solubility and dissolution rate of poorly soluble drugs by using hydrophilic water insoluble carriers.The present study aims to enhance the solubility and dissolution rate of EBS by using surface solid dispersion technique. Avicel® PH101, Avicel® PH 102, croscarmellose sodium(CCS) and sodium starch glycolate(SSG) were used as water insoluble hydrophilic carriers.The SSD formulations of EBS were prepared by the solvent evaporation method in different drug: carrier weight ratios and evaluated for their percentage yield, drug content , water solubility, dissolution study in 0.1 N HCl, crystal lattice using powder X-ray diffraction (PXRD) and Fourier Transform Infrared Spectroscopy (FTIR) for determination the drug-carrier interaction.Most of the prepared SSD formulas showed improvement of drug solubility. The best result was obtained with formula SSD16 (EBS:CCS 1:15) that showed high percentage yield (98.5%), high drug content (98.39%) and 8.2 fold increase in solubility compared to solubility of pure drug with improved dissolution rate. The drug was converted to amorphous form without chemical interaction with the carrier.